Evaluating the color stability of 3D-printed resins against various solutions - Arash Shishehian; Farnaz Firouz; Sara Khazaee; Hossein Rajabi; Maryam Farhadian; Fatemeh Niaghiha (PAGEPress Publications, 2023)
The purpose of this study was to investigate the effect of different solutions on the optical behavior of two types of 3D-printed resin (Detax and Asiga). The samples were randomly divided into 4 groups of cola, orange juice, tea and artificial saliva (control group) in the form of 14 x 10 mm blocks with a thickness of 1.5 ± 0.3 mm (10 samples in each group). By spectrophotometric device, the color of the examined samples was recorded in the CIE system and in three parameters *L (brightness), a* (red-green) and b* (blue-yellow) as the initial record. The color difference of the samples was recorded on 7 and 30 days after immersion as a secondary record. After that, using the formula, the color difference (ΔE) were calculated. T-test also was used to analyze the data. There was no significant difference between the amount of ΔE on 7th and 30th days after exposure to artificial saliva and cola and on 7th days after exposure to orange juice and tea. But on the 30th day, a significant difference was found in orange juice and tea drinks (p<0.05), so that the value of ΔE in Asiga printer was lower than Detax. ΔE changes in orange juice solution were more than other drinks. On the 30th day of immersion in tea drinks and orange juice, Asiga printer had significantly less color difference than Detax printer.